The efficacy of Vespex® wasp bait to control Vespula species (Hymenoptera: Vespidae) in New Zealand. Issue 3 (3rd July 2017) - Edwards, Eric; Toft, Richard; Joice, Nik; Westbrooke, Ian
ABSTRACT: Transitioning from trials to pest control tool, the efficacy of controlling wasps Vespula vulgaris and V. germanica using Vespex® wasp bait was tested in 2015. Vespex® is a protein-based bait matrix with 0.1% fipronil. Five sites ranging <300 to >2000 ha and over 5500 ha in total had bait stations placed 300 × 50 m apart and received one application of Vespex®. Wasp nest traffic rates declined 93% in four days at one site, and over 97% after 20–38 days at all other sites. Measured honeydew availability also improved post wasp control. Further demonstrating feasibility, five different agencies worked closely with government leading many programme aspects. Vespex® was made more widely available in New Zealand towards the end of 2015. Web page information showed ∼30% of all territorial authorities nationally are engaging in pest wasp problems. This signals a future potential in the way that pest wasps might be managed in a community context for social, economic and biodiversity conservation objectives.